Literasi Al-Qur’an Masyarakat Pedesaan: Studi Living Qur’an di Desa Ujong Tanoh Darat - Alfandi, Alwi; Hanif, Hanif; Firdaus, Muhammad (JISRev: Journal of Islamic Studies Review, 2026)
This study is motivated by the persistent issue of low-quality Qur’an recitation among the Muslim community in Ujong Tanoh Darat Village, despite the relatively high frequency of religious activities. Although most individuals are able to recite the Qur’an fluently, their recitation often does not conform to established tajwid principles. This research aims to examine Qur’anic recitation practices and to identify the underlying factors contributing to limited awareness of recitation quality through the Living Qur’an perspective. A descriptive qualitative approach was employed, utilizing participatory observation, in-depth interviews, and documentation as data collection techniques. The findings indicate that the majority of participants fall into the category of “fluent but incorrect in tajwid,” which is shaped by interrelated factors including family involvement, social environment, institutional religious structures, and entrenched habitual practices. The Living Qur’an perspective further reveals that the Qur’an is predominantly understood as a ritual practice and a symbol of social religiosity rather than as a text requiring precise phonetic and methodological observance. In conclusion, the phenomenon of inadequate Qur’anic recitation quality reflects a complex socio-religious dynamic that necessitates an integrated educational strategy involving family, community, and institutional reinforcement to enhance tajwid literacy sustainably.